1995
DOI: 10.1002/bip.360350405
|View full text |Cite
|
Sign up to set email alerts
|

The osmotic sensitivity of netropsin analogue binding to DNA

Abstract: The binding of a netropsin analogue to random sequence DNA, monitored by CD, is seen dependent on the concentration of neutral solutes. The binding free energy decreases linearly with solute osmolal concentration and the magnitude of the effect is insensitive to the chemical identity of the solute for betaine, sorbitol, and triethylene glycol. These solutes appear to modulate binding through their effect on water activity and changes in the hydration of the drug and DNA in the complex reaction, not through a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
33
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 31 publications
6
33
0
Order By: Relevance
“…By using two different model approaches, the Wyman linkage equation or the Gibbs Duhem equation, we found that 65-72 1 water molecules are linked to the binding of four oxygen molecules to human Hb under the experimental conditions used. Furthermore, this hydration change was found to be in agreement with the difference between the solvent-accessible surface areas of deoxy-and oxy-Hb computed from x-ray structures by Clothia et al (5,6).The experimental approach and analyses originally used by us to assess and quantify the role of water on the allosteric control of Hb have been tested in several other biochemical systems (7)(8)(9)(10)(11)(12)(13)(14). A standard linear dependence of equilibrium and kinetic free energy parameters on water activity rather than solute activity has been lately reported.…”
supporting
confidence: 77%
“…By using two different model approaches, the Wyman linkage equation or the Gibbs Duhem equation, we found that 65-72 1 water molecules are linked to the binding of four oxygen molecules to human Hb under the experimental conditions used. Furthermore, this hydration change was found to be in agreement with the difference between the solvent-accessible surface areas of deoxy-and oxy-Hb computed from x-ray structures by Clothia et al (5,6).The experimental approach and analyses originally used by us to assess and quantify the role of water on the allosteric control of Hb have been tested in several other biochemical systems (7)(8)(9)(10)(11)(12)(13)(14). A standard linear dependence of equilibrium and kinetic free energy parameters on water activity rather than solute activity has been lately reported.…”
supporting
confidence: 77%
“…(d ) Water as a less mobile part of molecular structure In DNA-drug (Sidorova & Rau 1995) and protein-DNA interactions, the stability of the complexes are osmotically sensitive. Even the specificity of the restriction enzyme EcoR1 is dependent on its osmotic environment (Robinson & Sligar 1993;Sidorova & Rau 1996).…”
Section: Systems That Have Been Interrogated With Osmotic Stressmentioning
confidence: 99%
“…Application of osmotic pressure is clearly a useful and versatile technique for studying the role of water in molecular recognition and is readily applied to the study of protein-DNA interactions (22,23,29,33). Typically application of osmotic stress favors formation of the protein-DNA complex, because a sizable dehydration of both molecules accompanies binding (22,23,33).…”
mentioning
confidence: 99%
“…Typically application of osmotic stress favors formation of the protein-DNA complex, because a sizable dehydration of both molecules accompanies binding (22,23,33). In the rare situations where water binding accompanies formation of the complex, osmotic stress weakens the interaction (29).…”
mentioning
confidence: 99%